Community awareness and participation in biodiversity conservation at Phong Nha-Ke Bang National Park, Vietnam (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Truong DD. 2021. Community awareness and participation in biodiversity conservation at Phong Nha-Ke Bang National Park, Vietnam. Biodiversitas 23: 583-594. Local community's perception and attitude towards biodiversity conservation are essential to the sustainable management of national parks in Vietnam. The conservation of biodiversity in national parks is facing pressures from economic development activities, which has led to the degradation of the ecological values ??of the national parks. People's awareness and their participation in conservation management are crucial to the sustainable management of national parks. This study examined the awareness and participation of local people in biodiversity conservation at Phong Nha-Ke Bang National Park (PN-KBNP), Vietnam. PN-KB is one of the national parks with the highest biodiversity values ??in Vietnam and is recognized by UNESCO as a world heritage site. To assess participation in conservation management, the study implemented a Contingent Valuation Method for estimating the willingness to pay of households in the buffer zone for biodiversity conservation in PN-KBNP. A survey was implemented to 358 households randomly selected in five communes adjacent to the park. Focus group discussions and in-depth interviews with selected key informants were also practiced for the management of insight information. The result showed that local villagers generally hold a fairly high perception of biodiversity values and positive attitudes towards biodiversity conservation at PN-KBNP. This positive perception comes from the close interaction between household livelihoods and the national park on a daily basis. However, awareness of national park management rules are not high. In addition, local people are willing to sacrifice part of their income to conserve biodiversity for current and future generations. On an average, each household was willing to pay 297,000 VND/year for biodiversity conservation. Payment levels, age, length of residency and education were observed to significantly impact on villagers' participation in biodiversity conservation initiatives. The balance between development and conservation was found to be the key in Park management, where communities need to be given more power to plan, monitor and implement conservation activities while establishing clear forest land user right for households and communities.